Aggregation-induced changes in the chemical exchange saturation transfer (CEST) signals of proteins - Görke, Steffen; Kunz, Patrick; Mogk, Axel; Bukau, Bernd; Ladd, Mark E.; Bachert, Peter (NMR in biomedicine, 2017)
Chemical exchange saturation transfer (CEST) is an MRI technique that allows mapping of biomolecules (small metabolites, proteins) with nearly the sensitivity of conventional water proton MRI. In living organisms, several tissue-specific CEST effects have been observed and successfully applied to diagnostic imaging. In these studies, particularly the signals of proteins showed a distinct correlation with pathological changes. However, as CEST effects depend on various properties that determine and affect the chemical exchange processes, the origins of the observed signal changes remain to be understood. In this study, protein aggregation was identified as an additional process that is encoded in the CEST signals of proteins. Investigation of distinct proteins that are involved in pathological disorders, namely amyloid beta and huntingtin, revealed a significant decrease of all protein CEST signals upon controlled aggregation. This finding is of particular interest with regard to diagnostic imaging of patients with neurodegenerative diseases that involve amyloidogenesis, such as Alzheimer's or Huntington's disease. To investigate whether the observed CEST signal decrease also occurs in heterogeneous mixtures of aggregated cellular proteins, and thus prospectively in tissue, heat-shocked yeast cell lysates were employed. Additionally, investigation of different cell compartments verified the assignment of the protein CEST signals to the soluble part of the proteome. The results of in vitro experiments demonstrate that aggregation affects the CEST signals of proteins. This observation can enable hypotheses for CEST imaging as a non-invasive diagnostic tool for monitoring pathological alterations of the proteome in vivo.